When Funding Meets Practice: The Fate of Contemporary Therapeutic Approaches and Self‐Determination in a Consumer‐Centred Disability Funding Scheme. Issue 4 (December 2016) - McDonald, Myfanwy; Davis, Kate; Mahar, Nicole
Abstract: This article highlights the potential for a consumer‐centred model of funding (the Australian National Disability Insurance Scheme, or the NDIS), to undermine therapeutic approaches in Early Childhood Intervention (ECI) that facilitate self‐determination amongst young children with a disability or developmental delay and their families. This process of undermining is not intentional but a consequence of deeply held cultural assumptions regarding how health care should be delivered and assessed. The article brings together multiple "strands" of evidence and theory regarding self‐determination, disability funding, therapeutic approaches within ECI, and cultural beliefs regarding health to demonstrate how a funding model founded on the principle of self‐determination could potentially undermine a therapeutic approach that supports the very same principle. The potential for this consumer‐centred disability funding (CCDF) scheme to undermine contemporary therapeutic approaches highlights a significant challenge—how to communicate the complexity of the evidence regarding effectiveness of different therapeutic approaches to parents of children with a disability without overwhelming them, and how to ensure that this CCDF scheme facilitates informed, meaningful choices for families.